2020
DOI: 10.24018/ejeng.2020.5.9.2058
|View full text |Cite
|
Sign up to set email alerts
|

Design of Potential SARS-CoV-2 Inhibitor

Abstract: This computational study comprises of pharmacophore-base virtual screening of the ZINC database, molecular docking of predicted ligands (pharmacophore agent) against the target protein, SARS-CoV-2 (PDB ID: 5r7y) and the prediction of ADMET descriptors using Swiss ADME and PROTOX-II online web servers.  Meanwhile,  remdesivir, ZINC72392503, ZINC72809903, ZINC06560017, ZINC76101700, ZINC88423098 and ZINC91600695 had a docking scores of -2.0 Kcal/mol, -6.7 Kcal/mol, -6.4 Kcal/mol, -6.0 Kcal/mol, -6.0 Kcal/mol, -6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The mean values observed for hydrogen bonds between the 2X08 and L3 inhibitor were determined for complete trajectories using MD technique. The aforementioned observation indicated that the complex exhibited stability under the physiological conditions [53].…”
Section: H-bond Interaction Analysesmentioning
confidence: 94%
“…The mean values observed for hydrogen bonds between the 2X08 and L3 inhibitor were determined for complete trajectories using MD technique. The aforementioned observation indicated that the complex exhibited stability under the physiological conditions [53].…”
Section: H-bond Interaction Analysesmentioning
confidence: 94%